Sperm flagella: comparative and phylogenetic perspectives of protein components - Inaba, Kazuo (Molecular human reproduction, 2011)
Sperm motility is necessary for the transport of male DNA to eggs in species with both external and internal fertilization. Flagella comprise several proteins for generating and regulating motility. Central cytoskeletal structures called axonemes have been well conserved through evolution. In mammalian sperm flagella, two accessory structures (outer dense fiber and the fibrous sheath) surround the axoneme. The axonemal bend movement is based on the active sliding of axonemal doublet microtubules by the molecular motor dynein, which is divided into outer and inner arm dyneins according to positioning on the doublet microtubule. Outer and inner arm dyneins play different roles in the production and regulation of flagellar motility. Several regulatory mechanisms are known for both dyneins, which are important in motility activation and chemotaxis at fertilization. Although dynein itself has certain properties that contribute to the formation and propagation of flagellar bending, other axonemal structures-specifically, the radial spoke/central pair apparatus-have essential roles in the regulation of flagellar bending. Recent genetic and proteomic studies have explored several new components of axonemes and shed light on the generation and regulation of sperm motility during fertilization.